Cultural background and Bender Visual Motor Gestalt test performance : comparison of the performance of Xhosa and white South African adolescents using the Pascal-Suttell scoring system - Horn, Stuart George (Rhodes University, Faculty of Humanities, Department of Psychology)
The quality of the Bender-Gestalt performance of 22, normal, white South African male adolescents and 22, normal, Xhosa male adolescents, aged between 17 and 22 years, was investigated. The Pascal-Suttell scoring system was used. The mean score of the white adolescents was significantly below that of the Xhosa adolescents. It was found that while the mean score of the Xhosa adolescents was within one standard deviation of Pascal and Suttell's normative 'high school' mean, the mean score of the white adolescents was below that of the normative mean and not within one standard deviation of the mean. The results lend support to the findings that Bender performance is related to cultural background. It is suggested that the Pascal-Suttell tables may be in need of revision. The advisability of standardising tables, which are culture specific, for clinical useÂ· in the Southern African context, is indicated.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Bender-Gestalt Test; Teenagers -- Psychological testing -- South Africa; Xhosa (African people) -- Psychology; Black people -- Psychological testing -- South Africa